Single-nuclei RNA-seq on human retinal tissue provides improved transcriptome profiling - Qingnan Liang (Nature Portfolio, 2019)
The retina is a heterogeneous tissue composed of multiple cell types. Via single-nuclei RNA sequencing on human neural retinal tissue, the authors characterise the transcriptome profile for individual cell types in the human retina.